REVIEW ON STATIC & DYNAMIC ANALYSIS OF AEROFOIL BLADE AT DIFFERENT ASPECT OF RESEARCH INVESTIGATION - Narendra D. Khairnar; Dr. Avinash D. Bagul; Satish Gambhir Borase (International Engineering Journal For Research & Development, 2024)
An optimised designed of air foil blade is required for highest quantity of wind power along with both to increase lift and reduce drag, as a whole research area have to be enhanced to the static & aerodynamic performances. To improve the aerodynamics of blade, aerofoil design is crucial. The efficiency of aerodynamics of the blade is requires to be balanced with the loads on the system. So, several geometric specifications are required to solve problem, not just one. But other factors like Aerofoil combination legacy and different function of blade. The geometrical and operational characteristics like speed ratio of tip, velocity of wind, robustness, blade number and shape of blade are also taken into account. The span of aerofoil blade aerodynamic helps in decrease of noise, control over stall condition during dynamic response, independent properties, along unstable condition with distorted air flow state. Conventional instruments for theoretical work of dynamic methods like stage charts, diagrams of bifurcation along with containers are applied for examine & comprehends, the dynamic response exbits common aerofoil part. Steady-straight jet with given momentum coefficient, is the least effective technique, while the control performance of a steady-angled jet is superior. Due to the creation of stream wise voices that in order to energize the boundary layer, which combines maximum velocity fluid along minimum velocity fluid close the wall. Increasing pressure and decreasing downstream flow separation allowed the unsteady-oscillating jet to operate at highest efficiency.